Influence of the Korean wave on purchasing intentions of Korean products / Nurul Syahirah Abdullah, Nur Alin Yasmin Azam and Noor Aisyah Idris - Abdullah, Nurul Syahirah; Azam, Nur Alin Yasmin; Idris, Noor Aisyah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This study aims to identify whether the Korean waves (K-Drama, K-Pop, KFood, K-Beauty and K-Fashion) and gender influences consumers purchasing intention for Korean products. This study used a quantitative research method to gather quantifiable data from the online survey with a total of 252 respondents who participated in the survey. High quality, beauty, and trend were the top three considered factors when purchasing Korean products. The study also found that Korean products are mostly bought once a month, with a monthly spending of less than RM 50. Multiple linear regression was used to determine the significant influences of the Korean Wave and gender on consumer’s purchasing intention for Korean products. The results showed that only K-Drama, K-Beauty and K-Fashion have a significant influence on consumers’ buying intention towards Korean products that they have purchased. The study also found no significant difference in students’ purchasing intentions for Korean products among the three faculties (Kolej Pengajian Pengkomputeran Informatik dan Matematik (KPPIM), Fakulti Sains Pentadbiran dan Pengajian Polisi (FSPPP), Fakulti Sukan dan Rekreasi (FSR)), suggesting faculty affiliation doesn’t impact their purchasing decisions. Therefore, the facilitated digital era plays an important role in spreading Korean content on social media and plays a vital role in influencing consumer’s purchasing intention. Researchers suggested that, should use a larger sample size and longitudinal studies to understand the effects of the Korean Wave on youth purchasing behaviors. As a result, this research can gain insight into how the Korean wave influences consumer purchasing patterns and the intention to purchase Korean products.